2012
DOI: 10.1088/0004-6256/144/3/79
|View full text |Cite
|
Sign up to set email alerts
|

Optical and X-Ray Observations of the Merging Cluster As1063

Abstract: We present the first in-depth analysis of the massive cluster AS1063. This is one of the hottest X-ray clusters discovered to date and is undergoing a major merging event. The average temperature of the hot intracluster medium has been measured, using Chandra/ACIS-I, and found to be >11.5 keV. Optical spectroscopy, from GMOS-S, has provided a mean redshift of 0.3461 and a large velocity dispersion of 1840 +230 −150 km s −1 . Both the large velocity dispersion and high X-ray temperature suggest a very massive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 42 publications
12
57
0
Order By: Relevance
“…Like the other Frontier Field clusters, its map of galaxy density shows significant substructure, with an X-ray peak offset from the primary peak of galaxy density (Gómez et al 2012). Weak-lensing analysis also identified multiple substructures, and gives a mass of the central cluster in agreement with X-ray and SZ calculations (Gruen et al 2013).…”
Section: Abell S1063mentioning
confidence: 57%
See 2 more Smart Citations
“…Like the other Frontier Field clusters, its map of galaxy density shows significant substructure, with an X-ray peak offset from the primary peak of galaxy density (Gómez et al 2012). Weak-lensing analysis also identified multiple substructures, and gives a mass of the central cluster in agreement with X-ray and SZ calculations (Gruen et al 2013).…”
Section: Abell S1063mentioning
confidence: 57%
“…Abell S1063 (also known as RXC J2248.7-4431 and SPT-CL J2248-4431), is the southernmost Frontier Fields cluster with z=0.3461 (Abell et al 1989;Böhringer et al 2004;Gómez et al 2012). Abell S1063 is a massive cluster with a large velocity dispersion .…”
Section: Abell S1063mentioning
confidence: 99%
See 1 more Smart Citation
“…Gómez et al (2012) indicates that the galaxy cluster has undergone a recent off-axis merger, and Melchior et al (2015) find the cluster to be embedded in a filament with corresponding orientation. However, moderately deep X-ray Chandra observations show an elongated but regular shape, with no evidence of massive substructures in the inner region (see Fig.…”
Section: Rxc J2248mentioning
confidence: 99%
“…For example, the galaxy at the center is clearly the BCG, unlike other clusters which have multiple galaxies of relatively equal brightness. Yet it may be more complicated than it appears: dynamical studies have shown that it could be going through a merging event (Gómez et al 2012). Our models are able to fit the data with only two halos, the fewest of the HFF clusters.…”
Section: Abell S1063mentioning
confidence: 91%